ON “MAKING ODDKIN” IN SARA BAUME’S “SPILL SIMMER FALTER WITHER” - BORBELY, Carmen-Veronica (Studia Universitatis Babeș-Bolyai Philologia, 2018)
On “Making Oddkin” in Sara Baume’s Spill Simmer Falter Wither. This study argues that in its figuration of the protagonist’s complex engagement with the dog that enables him to articulate his autobiographical self, Sara Baume’s 2015 novel Spill Simmer Falter Wither adopts a critical posthumanist stance on the abyssal rift conventionally understood to separate human and non-human animals. Tapping the potential for dismantling the anthropocentric mindset, the odd kinship Ray forms with One Eye becomes a way of disrupting essentialist conceptions of selfhood and articulating alliances that catalyse the narrator’s reconciliation with personal trauma and his ethically responsible repositioning in the world at large. Rezumat. “Înrudiri bizare” în romanul “Spill Simmer Falter Wither” de Sara Baume. Argumentul studiului de față este acela că prin configurarea unei relații de ordin simbiotic între câine, ca specie de companie, și protagonist, ca animal autobiografic, romanul Spill Simmer Falter Wither (2015) de Sara Baume se raliază unei poziții critic-postumaniste asupra faliei abisale care, în mod conventional, trasează linia de demarcație între uman și nonuman. Având potențialul de destabilizare a mentalității antropocentrice, straniile alianțe dintre Ray și One Eye devin o modalitate de bruiere a concepțiilor identitare esențialiste, proximitatea animalului catalizând reconcilierea naratorului cu trauma personală și repoziționarea sa etic-responsabilă în lume. Cuvinte cheie: Sara Baume, ficțiunea gotică, creaturile de companie, Donna Haraway, stranii alianțe, Jacques Derrida, l’animot